EQUINE GASTEROPHILOSIS IN THE REPUBLIC OF KARAKALPAKSTAN UNDER ARID CLIMATE CONDITIONS. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article presents information on the biological development of Gasterophilidae family members, which are obligatory parasitic insects, in the digestive system of horses raised in the conditions of the Republic of Karakalpakstan. It discusses the impact of arid climate conditions on their lithogenesis, the bioecological characteristics of the causative agents of gasterophilosis, their distribution, invasion intensity, and extensiveness, as well as their resistance to various anthelmintic medications.